Average OH density in alternating current dielectric barrier discharge by laser-induced fluorescence technique. (25th September 2015) - Yang, Hongliang; Feng, Chunlei; Gao, Liang; Ding, Hongbin
Abstract: The average OH density in atmospheric He–H2 O(0.4%) needle-plate dielectric barrier discharge (DBD) was measured by the asynchronous laser-induced fluorescence (LIF) technique and the fluctuation of OH radical density was measured simultaneously to prove that the average OH density can be obtained by the asynchronous LIF technique. The evolution of the average OH density in four different discharge patterns, namely, negative barrier corona discharge, glow discharge, multi glow discharge, and streamer discharge, was studied, and it was found that the average OH density has an observable increase from corona discharge to streamer discharge. The main mechanism of OH production in the four different discharge patterns was analyzed. It was shown that the main mechanism of OH production in negative barrier corona discharge is electron direct collision dissociation, whereas in the other three discharge patterns the He metastable Penning ionization is the main process.